Estresse pela aplicação de radiação UV-C e o déficit hídrico em genótipos de tomate Micro-Tom - Hüther, Cristina Moll (2014)
The objectives of this study were: a. to compare growth and yield components of Micro-Tom tomato plants with wild plants and transformed plants for different levels of MT-sHSP23.6 expression (mitochondrial small heat shock proteins); b. to verify damages caused by UV-C application to photosynthetic activity, in the vegetative and reproductive stages, with the same genotypes previously described; c. to compare the effects of water deficit on photosynthetic activity in Micro-Tom tomato plants with the genotypes reported, in the period of floral induction. The first experiment was carried out in growth chambers, under controlled conditions. The analyses were performed at regular time intervals of 21 days. Collections started on 21st day after the transplant, a total of six collections. Leaf area, dry weight of the plants parts, and the number of green and red fruits were determined. From the results obtained we verified that the genetic transformation of this variety did not interfere significantly with these plants growth. In the second experiment that aimed to evaluate the effect of application of UV-C radiation, two trials were performed; the plants were grown in a green house, under controlled temperature and humidity. In the first trial the application of UV-C radiation was performed only once, when the plants were in vegetative stage. In the second trial the plants were exposed to two doses of UV-C radiation, with an interval of ten days, the application began when the plants were starting the reproductive stage. The application lasted two minutes with a dose of 0,5kJ.m-2. Chlorophyll index, chlorophyll a fluorescence, and gas exchanges were evaluated. At the first trial, the evaluations were performed at 16, 64, 168, and 336 hours after the application of the radiation, and in the second trial at 16, 64, and at 168 hours after first application, with the same interval after the second application of radiation. From the results we observed that the genotypes showed different behaviors in relation to the data of transient fluorescence. However, the net assimilation rate was more affected in the transformed genotypes, with greater intensity in the second trial, especially after the second application. We noticed that in both trials genetic transformation did not contributed significantly to provide better performance under these experimental conditions. In the third trial the plants were grown in a growth chamber. Fortyfour days after sowing, in floral induction period, they were submitted to water deficit for five days. Chlorophyll index, chlorophyll a fluorescence, and gas exchanges were evaluated, and at the end of the experiment we made simultaneous analysis of fluorescence decrease, modulated reflection at 820 nm, proline content in the foliar area, and dry matter of plant parts. We could verify that genotype with over-expression of MT-sHSP23.6 was more efficient than the other genotypes in photochemical reactions, allowing that water deficit data were smaller, however it was not possible to identify the relation of the over-expression of these proteins with the parameters of gas exchange.